Competence beliefs and perceived ability evaluations: how do they contribute to intrinsic motivation and achievement? - Freiberger, Verena; Steinmayr, Ricarda; Spinath, Birgit (Learning and individual differences, 2012)
To study the role of students' competence beliefs and their perceived teachers' ability evaluations for intrinsic motivation and achievement in math, 459 second graders from 27 German classrooms were examined. Students provided self-reports on their intrinsic motivation, competence beliefs and perceived teachers' ability evaluations in math. Teachers gave insight in students' math grades. Relations were analyzed by three different models: a direct, an indirect and an interaction effect model. Concerning intrinsic motivation, results provided support for both an indirect effect and an interaction effect model, but not for a direct effect model. With regard to math achievement, only the indirect model appeared to be appropriate. The finding that perceived teachers' ability evaluations had an (indirect) effect on students' intrinsic motivation and achievement in math hints at the role of significant others in the development of children's academic functioning and might guide potential interventions.
Gesehen am 30.04.2018